2009
DOI: 10.1180/minmag.2009.073.6.943
|View full text |Cite
|
Sign up to set email alerts
|

Megacrysts and salic xenoliths in Scottish alkali basalts: derivatives of deep crustal intrusions and small-melt fractions from the upper mantle

Abstract: ABSTR ACTCa-poor and typically Na-rich feldspar megacrysts are common associates of spinel lherzolitic and pyroxenitic xenoliths in Scottish alkalic basalts. Associated megacrysts and composite megacrysts and salic xenoliths include apatite, magnetite, zircon, biotite, Fe-rich pyroxene(s) and corundum. The salic xenoliths and related megacrysts are referred to collectively as the 'anorthoclasite suite': the majority of the samples are inferred to derive from the disaggregation of coarse-grained, typically Na-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 72 publications
(113 reference statements)
5
14
0
Order By: Relevance
“…Similar models for corundum origin from upper mantle to lower crustal, fractionated syenitic/anorthoclasitic magma are also proposed for other sapphire occurrences (e.g. Coenraads et al 1995;Sutherland et al 1998Sutherland et al , 2009Upton et al 1999Upton et al , 2009Graham et al 2008).…”
Section: Fig 7 Oxygen Isotope Values (supporting
confidence: 63%
“…Similar models for corundum origin from upper mantle to lower crustal, fractionated syenitic/anorthoclasitic magma are also proposed for other sapphire occurrences (e.g. Coenraads et al 1995;Sutherland et al 1998Sutherland et al , 2009Upton et al 1999Upton et al , 2009Graham et al 2008).…”
Section: Fig 7 Oxygen Isotope Values (supporting
confidence: 63%
“…They propose that chlorite is formed by relatively low-temperature alteration of phlogopite by a late H 2 O and CO 2 -rich fluid exsolved from kimberlites. Upton et al (2009) describe chloritic rims around ocelli from a range of Scottish monchiquite/nephelinitic dykes, and ascribe these to separation of a carbonate-rich melt/fluid. A similar effect seems a very plausible process within Loch Roag dyke, and the occurrence of LREE-rich bastnäsite would be consistent with a carbonatitic melt/fluid.…”
Section: Rare-earth Elements Of the Sub-lewisian Lithospherementioning
confidence: 99%
“…They concluded that the majority of anorthoclase megacrysts (compositions in the range Ab 80-90 Or 20-10 ) are not phenocrysts, but crystallized from small-volume trachytic melts in the deep crust before being disaggregated and entrained by their host basaltic magmas. Based on the common association of these megacryst suites with alkaline basalt provinces, the presence of euhedral megacryst crystal forms and (limited) K-Ar and U-Pb data that suggest a close timing relationship between megacryst formation and host basalt magmatism, Upton et al (2009) suggested that the trachytic and basaltic magmas were broadly contemporaneous. However, some uncertainty remains about the exact location and nature of the host magma for the anorthoclase megacrysts.…”
Section: Discussionmentioning
confidence: 99%
“…This model was supported by Chapman and Powell (1976), who concluded that anorthoclase megacrysts (and associated cumulate nodules) formed from high-level differentiated magmas and were subsequently transported to the surface by later more basic magmas. Upton et al (2009) investigated megacrysts and xenoliths, including an anorthoclasite suite, from alkali basalts in Scotland. They concluded that the majority of anorthoclase megacrysts (compositions in the range Ab 80-90 Or 20-10 ) are not phenocrysts, but crystallized from small-volume trachytic melts in the deep crust before being disaggregated and entrained by their host basaltic magmas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation